Pengaruh Pemanfaatan Hutan Mangrove sebagai Sumber Belajar IPA terhadap Sikap Peduli Lingkungan Siswa Kelas IV SD Kota Bengkulu - Saputri, Dara Nery; Winarni, Endang Widi; Gunawan, Ansyori (UNIB Press, 2019)
The objective of this research is to find out the effect of mangroves usage as the science sources toward the students attitude of caring for the environment (a case study at the fourth grade of elementary school in Bengkulu city). In term of methodology, the researcher used quantitative. Research design in this research used quasi experimental with kind of design using The Matching Only Pretest-Posttest Control Group Design. The subject of the research is the fourth grade students in Bengkulu city. The population is the whole elementary school whose still use KTSP as the curriculum. The test was given to experiment and control class. The questionnaire sheet which consist of declaration’s attitude was given at the pretest and posttest. This questionnaire sheet is used as the instrument of the research. The data was analysed using descriptive and inferential analysis which is uji-t. The result of the research showed that the average score of the students posttest from experiment and control class was 98,47 and 91,42. The result of uji-t with thitung 2,59and ttabel 2,005. Therefore thitung>ttabel, it can be concluded that the effect or the influence of mangroves usage as the science sources toward the students attitude of caring for the environment (a case study at the fourth grade of elementary school in Bengkulu city) is significant. It’s indicate that the election of study sources which contextual and the processing of the good study sources with persuasive message, also attractive for elementary students can be influential toward their attitude.